2020
DOI: 10.1161/hypertensionaha.119.14280
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive Complications of Pregnancy and Risk of Venous Thromboembolism

Abstract: Hypertension during pregnancy and preeclampsia are associated with increased arterial thrombotic risk in later life. Whether these complications are associated with risk of venous thromboembolism (VTE) on the short term after pregnancy and on the long term, that is, outside pregnancy, is largely unknown. We conducted a nationwide cohort study in women with at least 1 pregnancy and their first VTE risk by linking the Dutch perinatal registry (Perined) to anticoagulation clinics. We used Cox proportional hazard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 23 publications
1
50
0
1
Order By: Relevance
“…Hormonal methods may be safe in women with stable graft function but are not recommended in women with hypertension or risk of thrombosis. Indeed, arterial hypertension during pregnancy is associated with increased arterial thrombotic risk [9]. All combined oral contraceptives investigated in an analysis were associated with an increased risk of venous thrombosis; the effect size depended both on the progestogen used and the dose of ethinylestradiol [10].…”
Section: Planning Posttransplant Pregnancymentioning
confidence: 97%
“…Hormonal methods may be safe in women with stable graft function but are not recommended in women with hypertension or risk of thrombosis. Indeed, arterial hypertension during pregnancy is associated with increased arterial thrombotic risk [9]. All combined oral contraceptives investigated in an analysis were associated with an increased risk of venous thrombosis; the effect size depended both on the progestogen used and the dose of ethinylestradiol [10].…”
Section: Planning Posttransplant Pregnancymentioning
confidence: 97%
“…El tromboembolismo venoso es una de las principales causas de morbilidad y mortalidad en gestantes ( 13), siendo más común en el embarazo y periodo posparto (14), debido al estado de hipercoagulabilidad que acompaña de forma fisiológica a la gestación como prevención de la hemorragia posparto (15). Múltiples factores de riesgo han sido identificados en el puerperio como causas de eventos trombóticos (16), entre estos se puede observar: un índice de masa corporal mayor a 25, inmovilidad, parto pretérmino, preeclampsia, hipertensión arterial, cesárea, infección posparto y hemorragia posparto (13,17).…”
Section: Discussionunclassified
“…In LMICs, results showed that overall 10-15% of direct maternal deaths are associated with preeclampsia (Khan et al, 2006;Duley, 2009). Hypertensive disorders of pregnancy includes chronic hypertension, gestational hypertension, and preeclampsia, and there is substantial evidence that these lead to adverse outcomes both during pregnancy and after birth (Berends et al, 2008;Rich-Edwards et al, 2010;Melchiorre et al, 2011;Mosca et al, 2011;Powers et al, 2012;Catov et al, 2013;Parikh et al, 2017;Whelton et al, 2018;Haas et al, 2019;Bergman et al, 2020;Boardman et al, 2020;Gooding et al, 2020;Scheres et al, 2020;Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%